Autophagic flux restoration of senescent T cells improves antitumor activity of TCR‐engineered T cells. Issue 9 (26th September 2022) - Zhang, Chaoting; Sun, Yizhe; Li, Shance; Shen, Luyan; Teng, Xia; Xiao, Yefei; Zhou, Ping; Lu, Zheming
Abstract: Objectives: Although adoptive cell therapy with T‐cell receptor‐engineered T cells (TCR‐Ts) has mediated effective antitumor responses in several cancers, senescence of T cells could impair the therapeutic effect of TCR‐Ts. Thus, it is essential to elucidate the characteristics of senescent TCR‐Ts and how to subsequently improve their antitumor effect. Here, we focused on the influence of autophagy on TCR‐Ts, since autophagy is tightly associated with the regulation of T‐cell activation, proliferation and differentiation. Methods: We first evaluated autophagy level of senescent TCR‐Ts, and then the senescent TCR‐Ts were expanded in vitro for 7 days with and without spermidine treatment, respectively. Furthermore, the proliferative potential, phenotypical characteristics and functionality of the propagated senescent TCR‐Ts were analysed in vitro and in vivo after 7‐day ex vivo expansion. Results: We found that autophagic flux of senescent TCR‐T cells was significantly impaired. The restoration of autophagic flux via spermidine treatment reduced the expression of inhibitory immunoreceptors (PD‐1, TIM‐3 or LAG‐3), enhanced proliferation and effector functions and subsequently demonstrated the superior in vitro and in vivo antitumor activity of TCR‐Ts. Conclusion: These data suggest that spermidine treatment presents an opportunity to improve the antitumor effect of TCR‐Ts for the treatment of solid tumors. Abstract : In our study, we found that autophagic flux of senescent T‐cell receptor engineered T cells (TCR‐Ts) was significantly impaired. The restoration of autophagic flux via spermidine treatment reduced the expression of inhibitory immunoreceptors (PD‐1, TIM‐3 or LAG‐3), enhanced proliferation and effector functions and subsequently demonstrated the superior in vitro and in vivo antitumor activity of senescent TCR‐Ts.